Cross-Talk Between the Tumor Microenvironment, Extracellular Matrix, and Cell Metabolism in Cancer - Nazemi, Mona; Rainero, Elena (Frontiers in Oncology, 2020)
The extracellular matrix (ECM) is a complex network of secreted proteins which provides support for tissues and organs. Additionally, the ECM controls a plethora of cell functions, including cell polarity, migration, proliferation and oncogenic transformation. One of the hallmarks of cancer is altered cell metabolism, which is currently being exploited to develop anti-cancer therapies. Several pieces of evidence indicate that the tumor microenvironment and the ECM impinge on tumor cell metabolism. Therefore, it is essential to understand the contribution of the complex 3D microenvironment in controlling metabolic plasticity and responsiveness to therapies targeting cell metabolism. In this mini-review, we will describe how the tumor microenvironment and cancer-associated fibroblasts dictate cancer cell metabolism, resulting in increased tumor progression. Moreover, we will define the cross-talk between nutrient signaling and the trafficking of the ECM receptors of the integrin family. Finally, we will present recent data highlighting the contribution of nutrient scavenging from the microenvironment to support cancer cells growth under nutrient starvation conditions.